Sovereign Bond Prices, Haircuts and Maturity - Asonuma, Tamon (IMF Working Papers; Working Paper ;, 2017)
Rejecting a common assumption in the sovereign debt literature, we document that creditor losses ('haircuts') during sovereign restructuring episodes are asymmetric across debt instruments. We code a comprehensive dataset on instrument-specific haircuts for 28 debt restructurings with private creditors in 1999-2015 and find that haircuts on shorter-term debt are larger than those on debt of longer maturity. In a standard asset pricing model, we show that increasing short-run default risk in the run-up to a restructuring episode can explain the stylized fact. The data confirms the predicted relation between perceived default risk, bond prices, and haircuts by maturity.